2020
DOI: 10.1136/bmjopen-2020-038437
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of integrated chronic care interventions for older people with different frailty levels: a systematic review protocol

Abstract: IntroductionFrailty poses a huge burden to individuals, their families and to healthcare systems. Several interventions have been evaluated for the improvement of outcomes for older people with frailty, including integrated care interventions. Reviews synthesising evidence on the effectiveness of integrated care for older people with frailty have treated them as a single population, without considering the heterogeneity between different frailty levels such as non-frail, mild frailty, moderate frailty and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Evidence is accumulating regarding interventions for frail older adults, including an integrated chronic care intervention with different frailty levels. A systematic protocol study is also being attempted [ 40 ]. Furthermore, as in a previous study [ 12 ] in which time intervention for stroke patients was found to be effective in improving life satisfaction and self-esteem, further studies of time use intervention that leads to improvement of SEMT, including life satisfaction of older adults, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating regarding interventions for frail older adults, including an integrated chronic care intervention with different frailty levels. A systematic protocol study is also being attempted [ 40 ]. Furthermore, as in a previous study [ 12 ] in which time intervention for stroke patients was found to be effective in improving life satisfaction and self-esteem, further studies of time use intervention that leads to improvement of SEMT, including life satisfaction of older adults, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…There is debate on how useful the electronic frailty index is, which was recommended for identifying people who are frail,6 7 how frailty is conceptualised by medical practitioners6 and what outcome measures are suitable to monitor impact of frailty on a person 8. Nevertheless, local frailty strategies are being put into action in the English NHS 9…”
Section: Introductionmentioning
confidence: 99%
“…The integration of health services and social services for senior residents has gained tremendous attention in recent years [ 5 ]. Evidence suggests that older people will have better health outcomes, enhanced satisfaction and decreased costs if a person-centered coordinated care is provided in the community [ 6 , 7 ]. Though widely acknowledged and pursued, several gaps in implementing such models exist.…”
Section: Introduction {6a}mentioning
confidence: 99%